Realizing Near‐Infrared Laser Dyes through a Shift in Excited‐State Absorption. Issue 6 (12th January 2021) - Aoki, Reiko; Komatsu, Ryutaro; Goushi, Kenichi; Mamada, Masashi; Ko, Soo Young; Wu, Jeong Weon; Placide, Virginie; D'Aléo, Anthony; Adachi, Chihaya
Abstract: The development of near‐infrared (NIR) light sources has attracted much interest due to their attractive applications, such as biosensing and light detection and ranging (LiDAR). In particular, organic semiconductor laser diodes with NIR emission are emerging as a next generation technology. However, organic NIR emitters have generally suffered from a low quantum yield, which has resulted in only a few examples of organic solid‐state NIR lasers. In this study, the authors demonstrate a highly efficient NIR emitter based on a boron difluoride curcuminoid structure, which shows a high photoluminescence (PL) quantum yield ( Φ PL ) at >700 nm and a high fluorescence radiative rate constant in a solid‐state film. Amplified spontaneous emission and lasing occurs at >800 nm with very low thresholds. The large redshift of the stimulated emission is attributed to the transition from the lowest excited state to the different vibrational levels of the ground state owing to the overlap between the emission and the singlet–singlet excited‐state absorption. Abstract : A new boron difluoride curcuminoid derivative shows a high photoluminescence (PL) quantum yield and good laser characteristics with low thresholds in the near‐infrared region. The light amplification occurs at longer emission wavelength than that expected from its PL spectrum. The analysis of the transient absorption spectroscopy indicates that the singlet–singlet excited‐state absorption causes the shift of laser wavelength.